MEDICINAL BIOMAGNETISMO IN THE TREATMENT OF PROSTATE CANCER: A CASE STUDY - Mara Rambo Martini, Angela; Neris Cazella, Luciane; Martini, Yuri; Viapiana Bossa, Adriane; Souza Santos, Jefferson (Health and Society, 2023)
Prostate cancer (PC) is reported as an important neoplasm worldwide, caused by the uncontrolled multiplication of cells in the prostate. The main risk factors are age over 50 years, family history, genetic susceptibility, hormonal disorders, obesity and environmental factors. Active surveillance of low-risk PC defers aggressive treatment until disease progression and is an increasingly recommended treatment strategy. This strategy aims to reduce costs and decrease treatment-related morbidity without affecting survival. Medicinal Biomagnetism (BM) is based on the distortion of the limit of homeostasis towards hyperacidity and hyperalkalinity of two specific points for each pathogenic microorganism or glandular dysfunction. The induction of loads that are in a vibrational and energetic relationship, by means of medium intensity magnets, greater than 1000 Gauss, corrects or prevents the distortion of the pH of the organs or tissues of the human body. In this way, the neutralization of pathogenic bioenergetic distortions promotes health. The aim of this study was to evaluate the effect of BM in the treatment of prostatic adenocarcinoma, prognostic group 1. After three sessions of BM, the levels of prostate-specific antigen (PSA) decreased and the prostate adenocarcinoma regressed to discrete chronic inflammation. This study represents the first in the evaluation of BM for the treatment of CP and may stimulate further studies in this field that are likely to yield important discoveries.